Pemanfaatan Tanaman Obat Keluarga (TOGA) dalam Pencegahan dan Pemulihan Penderita Akibat COVID-19 melalui KKN Tematik Universitas Halu Oleo (UHO) di Kabupaten Kolaka: Utilization of Family Medicinal Plants (TOGA) in the Prevention and Recovery of COVID-19 Sufferers by KKN Tematik of Universitas Halu Oleo (UHO) in Kolaka District - Idin Sahidin; Ruslin Ruslin; Sudarman Rahman (Jurnal Mandala Pengabdian Masyarakat, 2020)
Sufferers of Covid-19 in Southeast Sulawesi Province was continue to increase and until now there is no drug that can kill the virus. Therefore, to prevent, reduce and improve the recovery of Covid-19 cases is done by preventing and reducing the corona virus effects such as fever and shortness of breath. These activities include prevention from outside (external) using disinfectants and antiseptics, as well as prevention from within (internal) through increased immunity. Procurement of disinfectants, antiseptics, immune enhancements is done by utilizing family medicinal plants (TOGA) which can be scientifically justified. The method of this activity includes the socialization of the manufacture and use of disinfectants, handsanitisers and fresh drink made from TOGA in Sub-district of Watubangga, Regency of Kolaka through the Thematic Community Service (KKN) Program of Universitas Halu Oleo. TOGA used consists of turmeric (Curcuma domestica), lime (Citrus aurantifolia), betel (Piper bettle), lemongrass (Cymbopogon citratus), ginger (Curcuma xanthorrhiza) and ginger (Zingiber officinale).